FAKTOR-FAKTOR YANG MEMPENGARUHI PENGGUNAAN KONTRASEPSI METODE OPERASI PRIA (MOP) - Desak Ketut Sugiartini; Kadek Ayu Suarmini (JKM (Jurnal Kebidanan Malahayati), 2021)
FACTORS AFFECTING THE USED OF MAN CONTRACEPTION OPERATION METHOD  Background: The use of operation method of man contraception was still very little used, especially among husbands. Though the male operative method is very effective in terminating pregnancy. Operation method of man contraception was a method with a very high level of effectiveness. So the hoped that method of man contraception choice for couples if they intend to terminate the pregnancy. However, currently the use of method of man contraception is still very small, so it needs hard work to increase the use of method of man contraception. Purpose:The purpose of this study was to determine the dominant factors associated with the use of MOP in Bebetin Village. Methods:This type of research is quantitative research with the independent variables of education, knowledge, attitudes, family support and support from health workers. While the dependent variable is the use of the male operative method. The minimum sample size used was 68 respondents with the sampling technique used simple random sampling. This study used a questionnaire instrument in data collection. Then used enumerators assisted by posyandu and puskesmas in data collection. Analysis using chi-square then multivariate analysis used logistic regression. Result:The results of the study found that there was a relationship between family support and the use of male operation method (AOR: 7.4 95% CI 1.6-33.6) and support from health professionals (AOR: 4.5 95% CI 1.0-20.1). Meanwhile education, attitudes and knowledge are not related to the use of male operation method in Bebetin Village. Conclusion: The conclusion is that family support and health worker support are the dominant factors that husbands want to use male operation methodSuggestion: It is hoped that in the future support for family support and support for health workers will be increased while at the same time increasing the use of male operation method. Keywords : male operative method; contraception; behavior ABSTRAK Latar Belakang: Penggunaan kontrasepsi mantap masih sangat sedikit digunakan khususnya pada kaum suami. Padahal metode operatif pria (MOP) sangat efektif untuk menghentikan kehamilan. Penggunaan MOP merupakan metode dengan tingkat efektifitas yang sangat tinggi. Sehingga harapannya kontrasepsi mantap menjadi pilihan pasangan jika berniat untuk menghentikan kehamilan. Namun saat ini penggunaan MOP masih sangat kecil dilakukan sehingga perlu kerja keras dalam meningkatkan penggunaan MOP.Tujuan: Tujuan dari penelitian ini adalah mengetahui faktor dominan yang berhubungan dengan penggunaan MOP di Desa Bebetin.Metode: Jenis penelitian yang dilakukan adalah penelitian kuantitatif dengan variabel independent pendidikan, pengetahuan, sikap, dukungan keluarga dan dukungan tenaga kesehatan. Sedangkan variabel dependen adalah penggunaan metode operatif pria. Besar sampel minimal yang digunakan adalah 68 responden dengan Teknik pengambilan sampel secara simple random sampling. Penelitian ini menggunakan instrument kuesioner dalam pengumpulan datanya. Kemudian menggunakan enumeroator dibantu posyandu dan puskesmas dalam pengumpulan data. Analisis menggunakan chisquare kemudian analisis multivariat menggunakan regresi logistik.Hasil: Hasil penelitian menemukan bahwa terdapat hubungan dukungan keluarga dengan penggunaan MOP (AOR :7,4 95% CI 1,6-33,6) dan dukungan tenaga kesehatan (AOR :4,5 95% CI 1,0-20,1). Sedangkan pendidikan, sikap dan pengetahuan tidak berhubungan dengan penggunaan MOP di Desa Bebetin.Kesimpulan: Kesimpulannya bahwa dukungan keluarga dan dukungan tenaga kesehatan menjadi factor yang dominan suami mau menggunakan MOP.Saran: Diharapkan kedepannya dukungan keluarga dan dukungan tenaga Kesehatan semakin ditingkatkan sekaligus meningkatkan penggunaan MOP Kata kunci : metode operatif pria; kontrasepsi; perilaku